The Inter-Relationship between Prakriti, Diet, and Lifestyle: A Review - Bhandari, Sushant; Acharya, Achyut (International Research Journal of Ayurveda & Yoga, 2025)
Ayurveda, the ancient science of life, emphasizes personalized health through the concept of Prakriti (individual constitution). This constitutional type forms the basis for prescribing suitable diet and Lifestyle regimens to maintain health and prevent disease. It is considered an important concept of Ayurveda that explains individuality. Prakriti is a fundamental concept accepted by all Acharyas, falling into the category of Sarvtantra Siddhanta. The concept of Prakriti is scattered all over the texts, covering all aspects of health maintenance as well as disease manifestation. This review explores the interconnectedness of Prakriti, diet (Ahara), and Lifestyle (Vihara), referencing classical Ayurvedic texts. The understanding of this inter-relationship aids in disease susceptibility assessment, treatment planning, and promotion of holistic well-being. A deeper understanding of Prakriti allows practitioners to approach health in a truly individualized manner, integrating physical, psychological, environmental, and behavioral dimensions.